Modelling and sensitivity analysis of uncoordinated paired intersections with left-turn bays - Yao, Ronghan; Zhang, Wensong; Long, Meng (Transport, 2020)
Left-turn bays are often installed on the road segment between paired intersections. Such left-turn bays may reduce the approach capacities and impact on one another. Four optimization models are put forward for uncoordinated paired intersections with left-turn bays. The phase effective green times and the left-turn bay lengths are the decision variables, maximizing the intersection capacities, minimizing the intersection delays and both of them are respectively regarded as different objective functions, and minimizing the total delay for paired intersections is viewed as another objective function. The total capacity-to-delay ratio is defined to evaluate the operations of paired intersections as a whole. Using the field data, the sensitivities of the optimized outcomes to the weighting factors of the objective functions are analysed. To clarify the influences of different scenarios on traffic stream operations, seven scenarios are tested using VISSIM. The interval estimation and hypothesis testing are used to analyse the simulated data. Three concrete models are recommended to apply in practice with the procedure of model application being provided. The achievements can be applied to optimally assign the temporal-spacial resources for paired intersections when left-turn bays need to be installed and coordinated signals do not need to be considered. First published online 26 March 2020